Contradicciones normativas entre el código civil y la ley de seguridad social respecto a la inembargabilidad de los bienes constituidos en patrimonio familiar - Castillo Cedillo, Iván Saúl (2015)
In this thesis called "CONTRADICTIONS BETWEEN CIVIL CODE STANDARDS AND SOCIAL SECURITY LAW REGARDING THE GOODS UNSEIZABILITY INCORPORATED IN FAMILY HERITAGE", a study of the legal regulation of family assets is made in the legislation Ecuadorian. The Constitution of the Republic of Ecuador, to guarantee the rights of family members, contemplates a family property, which will feature inembargable is constituted. Also in the Ecuadorian Civil Code regulates the family heritage broadly, and the regulations confirms that the property constituting the same are provided indefeasible. But the rules of civil regime on the family estate, are in contradiction to what is stated in the Social Security Act, under which the goods are made in family assets can be seized in order to collect loans granted by the Ecuadorian Institute of Social Security. The contradiction found between the rules of the Civil Code and the Social Security Act, cause legal uncertainty and inconsistency between the existing rules in Ecuadorian society on the family estate, which violate the right to legal certainty is generated that sustains in the clarity of the laws that govern the country. At work concepts, scholarly opinions, analysis of national legislation and other countries, as well as the results of the reviews that were obtained by the technique of the survey and the interview, which allow to reach conclusions and make recommendations presented, concluding with the approach of the corresponding amendment to the Ecuadorian Civil Code, on the immunity from seizure of property constituting the homestead.